Assessment of Patient Satisfaction Among Pregnant Patients in The Out-Patient Department of Obstetrics and Gynecology Section at Metropolitan Medical Center Manila - Herry Prabowo Krestiyanto Widjaja (Jurnal Manajemen Kesehatan Indonesia, 2020)
ABSTRACT            Patient satisfaction reflects the quality of an institution’s delivery of health care services. Patient satisfaction is a critical factor in improvement or complete recuperation to wellness because satisfied patients will mean better compliance to treatment or follow up. As reported in the 2017 Annual OPD census of the Department of Obstetrics and Gynecology, there were 2617 total patient consultations. Majority of these (2138 or 81.7 %) were obstetrical cases. The average number of consultations per day (for Obstetrics and Gynecology patients combined) is 91. Therefore, the Out-Patient Clinic plays an important role in prenatal care specifically the prevention of adverse maternal and neonatal morbidity and mortality.            This study aimed to assess the level of patient satisfaction among obstetrical patients in the Out Patient Department of the Obstetrics and Gynecology Section at Metropolitan Medical Center from July 1, 2018 to July 31, 2018 and to see the relationship between socio-demographic characteristic and the level of patient satisfaction.            This is a descriptive, cross sectional study. The level of patient satisfaction assessed as to physical facilities, interaction between doctor and patient, interaction between nurses and patient, and registration service. There were sixty three subjects in this study. Sixty three  were satisfied with inclusion criteria. The validated questionnaire was the pretested questionnaire which was 96 % valid and reliable by Cronbach’s analysis.            Statistical analysis was done which showed respondents were generally satisfied. There were significant relationship association between socio-demographic characteristics and level of patient satisfaction with P value < 0.05.Key Word : Patient Satisfaction, Socio Demographic Characteristic